Aesthetic medicine growing tour practice - Kuechel, Marie Czenko (Quality Medical Publishing, 2009)
The practice of medicine is big business-unique in its blend of medicine, service, and retail sales. In today's competitive aesthetic market, providers of services must master the basic elements of running a business as well as develop a sound business model, respond to the challenges of a clinical practice, and meet their goals for building a thriving practice with satisfied, loyal patients